The integrated model of glutamate and dopamine hypothesis for schizophrenia: Prediction and personalized medicine for prevent potential treatment-resistant patients. (October 2020) - Huang, Li-Chung; Lin, Shih-Hsien; Tseng, Huai-Hsuan; Chen, Kao Chin; Yang, Yen Kuang
Abstract: Treatment-resistant schizophrenia (TRS) is one of the subgroups of schizophrenia of which little is known with regard to its optimal mechanism. Treatment response, either as full remission of symptoms or prediction by biomarker, is important in psychiatry. We have proposed a model that integrates dopaminergic and glutamatergic systems with the biological interactions of TRS patients. We hypothesize that the subgroups of schizophrenia may be determined by glutamatergic and dopaminergic concentrations prior to medical treatment. This hypothesis implies that higher glutamatergic concentration in the brain with normalized or decreased dopamine synthesis capacity may explain aspects of TRS as observed in clinical medical practice, neuroimaging measurements, and brain stimulations. According to this hypothesis, the ability to prescribe a proper medication combination, to predict the outcome in first-episode psychosis, and personalized medicine for chronic schizophrenia patients can be applied into practice. This represents an initial step in explaining psychosis due to the valence of two neurotransmitters. Future studies are needed to examine the validity of this mechanism.